2021
DOI: 10.1111/jgh.15734
|View full text |Cite
|
Sign up to set email alerts
|

Branching crypts in inflammatory bowel disease revisited

Abstract: Histologic sections from patients with inflammatory bowel disease (IBD) usually exhibit crypts with architectural distortions and branching crypts. It has been postulated that crypt branching should be assessed only in well‐oriented, upright crypts. However, those crypts are mostly found in sections from colectomy specimens and colon mucosectomies. Sections from endoscopic biopsies are fortuitously cut in a horizontal plane, a procedure mostly revealing cross‐cut crypt rings. In endoscopic biopsies from UC pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Although the pathophysiological mechanism for this phenomenon is not well understood, it could be due to compensation to inflammatory damage. 25 Furthermore, in experimental autoimmune encephalomyelitis, the ileal submucosa becomes thickened, as presented by Nouri and colleagues. 26 In EAU and non-immunized C57Bl/6J mice, we did not observe microscopic hemorrhage, crypt branching, or any gross intestinal abnormalities in the treatment groups.…”
Section: Resultsmentioning
confidence: 92%
“…Although the pathophysiological mechanism for this phenomenon is not well understood, it could be due to compensation to inflammatory damage. 25 Furthermore, in experimental autoimmune encephalomyelitis, the ileal submucosa becomes thickened, as presented by Nouri and colleagues. 26 In EAU and non-immunized C57Bl/6J mice, we did not observe microscopic hemorrhage, crypt branching, or any gross intestinal abnormalities in the treatment groups.…”
Section: Resultsmentioning
confidence: 92%
“…This possibility seems to be validated by the finding of crypt-associated anomalies interspersed with crypts in asymmetric branching. 16 ► That crypt-associated anomalies never reach the stadium of asymmetric branching as they are digested by mast cells and/ or gut microbiome proteases. 25 26 In conclusion, this survey describes a series of previously unreported anomalies evolving in crypts from the colon mucosa with inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of epithelial crests in ring-shaped cross-cut crypts identified the beginning of crypt branching. 16 Their results showed that the number of crypts in asymmetric branching surpassed that of crypts in symmetric branching. 14 Recently, while reviewing sections from patients with UC, a series of previously unreported cryptassociated histological anomalies were detected; they were regarded as histological artefacts.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations